The Microbial Revolution in the World of Joint Replacement Surgery - Srikrishnaraj, Arjuna; Lanting, Brent A.; Burton, Jeremy P.; Teeter, Matthew G. (JB & JS open access, 2024)
Background:The prevalence of revision surgery due to aseptic loosening and periprosthetic joint infection (PJI) following total hip and knee arthroplasty is growing. Strategies to prevent the need for revision surgery and its associated health-care costs and patient morbidity are needed. Therapies that modulate the gut microbiota to influence bone health and systemic inflammation are a novel area of research.Methods:A literature review of preclinical and clinical peer-reviewed articles relating to the role of the gut microbiota in bone health and PJI was performed.Results:There is evidence that the gut microbiota plays a role in maintaining bone mineral density, which can contribute to osseointegration, osteolysis, aseptic loosening, and periprosthetic fractures. Similarly, the gut microbiota influences gut permeability and the potential for bacterial translocation to the bloodstream, increasing susceptibility to PJI.Conclusions:Emerging evidence supports the role of the gut microbiota in the development of complications such as aseptic loosening and PJI after total hip or knee arthroplasty. There is a potential for microbial therapies such as probiotics or fecal microbial transplantation to moderate the risk of developing these complications. However, further investigation is required.Clinical Relevance:Modulation of the gut microbiota may influence patient outcomes following total joint arthroplasty.